Evaluation of customer satisfaction level at Prime Bank Limited, Tejgaon branch - Sharif, Md. Imran (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.